A study on the relationship between organizational learning and organizational commitment among employees at Eastern Pacific Industrial Corporation Berhad (EPIC) / Nik Nor Akma Ngah - Ngah, Nik Nor Akma (Faculty of Business and Management, 2019)
The study that was conducted was the title a study on the relationship between organizational learning and organizational commitment. The organizational learning was divided into four factors, which are motivation, leadership, innovation, and teamwork. Organizational learning refers to the process of developing, pertaining, and transforming knowledge within an organization while organizational commitment refers to the personal feeling toward the organization and was a perceived psychological status that individual to achieve their goals and motivation of loyalty a method. In this correlational research, the researcher focused on the relationship between organizational learning and organizational commitment at Eastern Pacific Industrial Corporation Berhad and the population was 196 according to Krejie and Morgan sample size and also using the simple random techniques on the Operation Department. The researcher has used questionnaires that consist three sections, which are Section A, Section B, and Section C. The data that had been collected will be analyzed using the Statistical Package for Social Science (SPSS) version 22.0. There was a positive relationship between organizational learning and organizational commitment with the moderate correlations (r=.527, p<0.05). Therefore, the recommendation from the researcher was suggested to improve the teamwork variables on employees at Eastern Pacific Industrial Berhad.